2004
DOI: 10.1016/s1078-5884(04)00114-5
|View full text |Cite
|
Sign up to set email alerts
|

Subintimal Angioplasty: Feasible and Durable

Abstract: Objective. To assess prospectively the feasibility and durability of subintimal angioplasty (SA) clinically and by duplex scans every 3 months. Patients and methods. Within a period of 54 months, we selected 96 patients with 100 occlusions (mean length: 11.5 cm) of femoro-popliteal or tibial arteries, for SA. Results. The technical success rate was 88% and seven out of 12 failures were treated by conventional surgery. Five belowthe-knee amputations were performed despite a patent recanalization. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 6 publications
(7 reference statements)
4
14
0
1
Order By: Relevance
“…12 Puskas et al reported a 34% incidence of surgical wounds of the lower limbs submitted to saphenous vein stripping for myocardial revascularization. 13 Subintimal angioplasty without stenting has been widely approached in the literature, [1][2][3][4][5][6][7][8][9][10][11] and is corroborated by our case report.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…12 Puskas et al reported a 34% incidence of surgical wounds of the lower limbs submitted to saphenous vein stripping for myocardial revascularization. 13 Subintimal angioplasty without stenting has been widely approached in the literature, [1][2][3][4][5][6][7][8][9][10][11] and is corroborated by our case report.…”
Section: Discussionsupporting
confidence: 80%
“…The evolution shown by this patient corroborates the high rates of limb salvation in series of subintimal angioplasty. [9][10][11] The patient had lymphangitis, which extended from the foot until the lower third of the thigh. This finding is a contraindication to revascularization by open technique, considering the potential complications of surgical wound.…”
Section: Discussionmentioning
confidence: 99%
“…This point estimate of the cost-effectiveness over 3 years generates a 'cost per QALY' of £134,257 [£3533/ (9.6/365. 25)].…”
Section: Three-year (Quality-adjusted) Analysismentioning
confidence: 99%
“…Priklausomai nuo imčių dydžio taikytas tikslusis Fišerio (mažoms imtims) ir asimptominis chi kvadrato (c 2 ) kriterijus. (28) 61 proc. T. Florenes (23) 69 proc.…”
Section: Po Angiografinio Tyrimo Papildomai Vertintaunclassified